Penguatan Kompetensi Guru dalam Merancang Pembelajaran Deep Learning yang Mindful, Meaningful, and Joyful di SD Muhammadiyah Merauke - Hanipah, Sri; Day, Wa Ode Siti Hamsinah; Hanip, Rival; Fredy, Fredy (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance the competencies of teachers at SD Muhammadiyah Merauke in designing and implementing deep learning that is mindful, meaningful, and joyful. The program focuses on strengthening teachers’ capacity to develop innovative lesson plans (RPP) and student worksheets (LKPD), design project-based learning activities, and utilize digital learning media grounded in local cultural contexts. The program was implemented through training and mentoring activities involving 25 teachers. Evaluation instruments consisted of a questionnaire comprising 25 items, and the data were analyzed using a t-test. The results indicate a significant improvement in teachers’ skills, with an increase of 18.48 points from a pre-training mean score of 72.84 to a post-training mean score of 91.32. These improvements reflect teachers’ enhanced ability to design deep learning–oriented instruction, produce 21st-century instructional tools, and apply innovative learning media in classroom practice. Overall, the program has the potential to serve as a model for sustainable professional development in fostering a humanistic and transformative learning ecosystem at SD Muhammadiyah Merauke.